Features and results of modeling surface stabilizer movable object - Сущенко, О.А.; Маляров, С.П.; Сайфетдінов, Р.А.; Янкелевич, Г.Є. (Proceedings of National Aviation University (archive), 2007)
The total mathematical model of the ground moving object stabilizer is considered. Features of creation of such class models are defined. Simulation results are represented and analysed.